Acute Portal Vein Thrombosis Treated with Recombinant Human Soluble Thrombomodulin Combined with Antithrombin III. (13th April 2020) - Nakayama, Satoshi; Murashima, Naoya
Abstract : Portal vein thrombosis is a major complication associated with liver cirrhosis. In cirrhotic patients, a decrease in procoagulant and anticoagulant factors and an unstable balance between them is observed, and a relative decrease in the activation of anticoagulant drivers is one of the main causes of portal vein thrombosis (PVT). Herein, we report a case of acute portal thrombosis associated with liver cirrhosis and treated with a recombinant form of soluble thrombomodulin (thrombomodulin alpha, TM- α ) in combination with antithrombin III. TM- α was administered in accordance with the dosage and route of administration for disseminated intravascular coagulation therapy and resulted in dissolution of PVT with a gradual decrease in D-dimer levels. No adverse events were observed during the course of treatment. In the future, in addition to conventional anticoagulation therapy using heparin or antivitamin K drugs, novel therapies targeting protein C activation using a recombinant form of soluble thrombomodulin may play an important role in the treatment of acute PVT.